Efikasi Diri, Situasi Ekonomi dan Latar Belakang Orang Tua terhadap Niat Tidak Berwirausaha Mahasiswa Gen Z di Surabaya - Okto Aditya Suryawirawan; Suhermin Suhermin; Wiwiek Srikandi Shabrie; Alfina Damayanti; Erina Febianti Trianjani (University of Merdeka Malang, 2023)
The purpose of this study was to analyze the effect of self-efficacy, economic situation, and parental background on gen z students’ entrepreneurial despondency. Non-probability purposive sampling was used to determine the respondent. The criteria of sample for this study were students who are in the age of 18-26 or categorized as gen Z. 150 respondents were acquired and used in this study. Data were analyzed using Mann-Whitney and Partial Least Square. The results confirmed that there were no differences in entrepreneurial despondency between gen z students without entrepreneurial parental background and gen z students with entrepreneurial parental background. Among the antecedent variables, only self-efficacy and economic situation that affected entrepreneurial despondency while parental background showed no effect. Economic situation and parental background failed to moderate the relationship between self-efficacy and entrepreneurial despondency. This study provided several theoretical and practical implication towards factors that affect entrepreneurial despondency among gen z students.